The characterization of a short chain dehydrogenase/reductase (SDRx) in Comamonas testosteroni. (2020) - Liu, Chuanzhi; Liu, Kai; Zhao, Chunru; Gong, Ping; Yu, Yuanhua
Abstract: C. testosteroni is a research topic that can degrade steroid hormones into water and carbon dioxide through a series of enzymes in the body. Short-chain dehydrogenase (SDR) are a class of NAD (P) H-dependent oxidoreductases in C. testosteroni . Its main function is catalyzing the redox of the hydroxyl/ketone group of the hormone. In this paper, a SDR gene( SDRx ) is cloned from C. testosteroni ATCC11996 and expressed. The polyclonal antibody was prepared and the SDRx gene knocked out by homologous recombination. Wild type and mutant C. testosteroni induced by testosterone, estradiol, estrone and estriol. The growth curves of the bacteria were measured by spectrophotometer. ELISA established the expression of SDRx protein, and high-performance liquid chromatography(HPLC) detected the contents of various hormones. The results show that the growth of wild type was faster than mutant type induced by testosterone. The concentration of SDRx is 0.318 mg/ml under testosterone induction. It has a great change in steroid hormones residue in culture medium measured by HPLC: Testosterone residue in the mutant type group was 42.4 % more than the wild type in culture medium. The same thing happens with induced by estrone. In summary, this SDRx gene involved in the degradation of testosterone and estradiol, and effects the growth of C. testosteroni .